EVALUATION OF THE PROPHYLACTIC ROLE OF INDIAN SHRIMP IN ALUMINUM CHLORIDE-INDUCED ALZHEIMER’S DISEASE ON EXPERIMENTAL RATS - S, RAMACHANDRAN; M, SRI RAMYA; U, LIZA; PS, LAKSHMI PRASANNA; K, SARISHMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This work was aimed to investigate the prophylactic and therapeutic role of Indian shrimp in aluminum chloride-induced Alzheimer’s disease (AD) in rats. Methods: The male Wistar rats were selected and divided into six groups. Group I received distilled water, Group II received AlCl3 ( 100 mg/kg, p.o.), Group III received rivastigmine (1 mg/kg, p.o.), Group IV received AlCl3 + shrimp powder (200 mg/kg, p.o), and Group V received AlCl3 + shrimp powder (400 mg/kg, p.o) for 60 days. At the end of the study, various parameters such as behavioral and biochemical investigations were assessed. Results: The result of the study shows that the shrimp (400 mg/kg) has better effect on the treatment of aluminum chloride-induced AD in rats. It showed a remarkable improvement in the behavioral and biochemical parameters, and the result of histopathology study shows that the hippocampus region of brain tissue recovered as compared with control. Conclusion: From this study, it is evident that dietary intake of shrimp can help to inhibit oxidative stress produced due to the accumulation of AlCl3 in the brain and used as a prophylactic for AD.